Mapping the electrostatic force field of single molecules from high-resolution scanning probe images - Prokop Hapala (Nature Portfolio, 2016)
The chemical properties of molecules are largely determined by the distribution of charge across them. Here, the authors demonstrate how the electrostatic force field, originating from the inhomogeneous charge distribution in a molecule, can be measured with sub-molecular resolution.